Nilai Gelombang Kejut Pada Pita Getar Dengan Menggunakan Metode Greenshileds - Yudi Asrin; Muhammad Idham; Lizar Lizar (Borneo Engineering : Jurnal Teknik Sipil, 2018)
The rumble strips phenomena in Indonesia aims to decrease speed and vibration effect for vehicles. Actually, the use of rumble strips in the Bengkalis island is not optimal, as does not reduce the speed of vehicles and always ignore the effect of the trill inflicted in the rumble strips for reasons of getting high speed and the less effect shakes posed. The purpose of this research is to find the shockwave on the road by using Greenshields method. Base on the result of this research, shockwave value as big as -30,299 km/h indicated the increase of vehicles in the rumble strips